The experimental investigation of the profit distribution in industrial supply chains with an outside option - Stein, Harald David; Ginevičius, Romualdas (Technological and Economic Development of Economy, 2010)
There is an industrial supply chain, where an individual customer selects a supplier and excludes other ones. If the excluded supplier has the possibility to overtake the relationship afterwards, he has big influence on the relationship among the cooperation partners. A profit distribution rule has been developed that considers the impact of the excluded supplier. The paper presents round based games in which the present values change and influence the cooperative relationships. First, examples with ideal‐typical numbers are calculated and depicted by the software “MATLAB”. Internet experiments are made with participants on the basis of the software “z‐tree” in order prove the relevance of the proposed profit distribution rule. Finally, the experimental data is compared with the theoretical predictions.Article in English.Pelno paskirstymo pramoninėse tiekimo grandinėse eksperimentinis tyrimasSantrauka. Paprastai pramoninio tiekimo grandineje klientas pasirenka konkretų tiekėja ir atmeta kitus. Jei veliau su atmestuoju tiekėju vis dėlto užmezgami santykiai, klientas įgyja didelę svarbą pletojant partnerių santykius. Sukurta pelno paskirstymo taisyklė, įvertinanti atmesto tiekejo įtaka. Straipsnyje pateikiama serija žaidimų, kuriuose kinta esama vertė ir daroma įtaka partnerių santykiams. Pirma, naudojantis MATLAB programinė įranga apskaičiuojamos ir atvaizduojamos būdingosios reikšmės. Antra, pasitelkus Z‐tree programinę įranga atliktas internetinis eksperimentas siekiant įrodyti, kad pasiūlyta pelno paskirstymo taisyklė galioja. Galiausiai eksperimentiniai duomenys palyginami su teorinėmis prognozėmis.Reikšminiai žodžiai: susitarimų stabilumas, pelno paskirstymo taisyklė, kraštinė sąlyga, eksperimentai, MATLAB,  Z‐tree.First published online: 10 Feb 2011